2011
DOI: 10.1016/j.jds.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prosthesis type and material on the stress distribution in bone around implants: A 3-dimensional finite element analysis

Abstract: Background/purpose: The design and materials of a prosthesis affect the loading of dental implants and deformation of the bone. The aim of the study was to evaluate the effects of prosthesis design and materials on the stress distribution of implant-supported prostheses. Materials and methods: A 3-dimensional finite element analysis method was selected to evaluate the stress distribution in the bone. Three different models were designed as follows: a 3-unit implant-supported fixed partial denture (FPD) compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
5
21
0
4
Order By: Relevance
“…elastic modulus, of FGBM implant is assumed to vary axially based on a single power-law function, but in this study, these properties are considered to change radially and axially according to single and two power-law functions, respectively. In all assessments, the maximum von Mises stress of the mandible bone appears near the neck of dental implant, which has a good agreement with reports of the previous literature [30][31][32][33][38][39][40][41][42][43][44]. In the radial FGBM case, a significant reduction in the maximum von Mises stress of the cancellous bone is observed in a way that this reduction leads to higher stability and faster bone regeneration, and as a result, the performance of dental implant system improves.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…elastic modulus, of FGBM implant is assumed to vary axially based on a single power-law function, but in this study, these properties are considered to change radially and axially according to single and two power-law functions, respectively. In all assessments, the maximum von Mises stress of the mandible bone appears near the neck of dental implant, which has a good agreement with reports of the previous literature [30][31][32][33][38][39][40][41][42][43][44]. In the radial FGBM case, a significant reduction in the maximum von Mises stress of the cancellous bone is observed in a way that this reduction leads to higher stability and faster bone regeneration, and as a result, the performance of dental implant system improves.…”
Section: Discussionsupporting
confidence: 89%
“…In the axial FGBM implant, according to Equation 2 and Figure 2B, as the mechanical properties, such as elastic modulus, increase from the bottom end to the top one, it was predictable that the maximum stress occurs in the superior region of the cancellous bone. Figure 7 indicates a good consistency compared to the reports from previous investigations [30][31][32][33][38][39][40][41][42][43][44].…”
Section: Resultssupporting
confidence: 82%
“…It has also been postulated that the viscoelasticity of bone compensates for any differential rigidity among the prosthetic materials (21). Higher values of MPS were observed in the cortical bone, which can be explained by its higher elastic modulus compared to the cancellous bone (12).…”
Section: Figmentioning
confidence: 99%
“…The materials used in framework fabrication have been suggested to be very important for biomechanical reasons. When loads are applied on the superstructure, stresses are created within them and transferred to the bone-implant interface, implant, and prosthetic components (12). They could influence the survival of the restoration and affect the bone stress distribution around implants (13).…”
Section: Introductionmentioning
confidence: 99%
“…16 Meric et al in 2011 concluded in a study that stress levels on the bone surrounding the implants were less in the case of fiber-reinforced resin than PFM. 17 In 2011, Gomes et al did a three-dimensional (3D) finite element analysis (FEA) which concluded the use of different materials to fabricate the superstructure for single implant-supported prosthesis did not affect the stress distribution in the supporting bone but the retention screw received less stress when a combination of porcelain and Zirconia was used. 18 Similarly, Solimon et al in 2015 conducted a 3D FEA which concluded that soft prosthetic materials absorb more energy from the applied load and transfers less energy to the bone.…”
Section: Discussionmentioning
confidence: 99%